Evolution of corporate social responsibility towards sustainability in Mexico 2013-2019 - Pérez Romero, Luis Alfonso (2022)
Since the Millennium Development Goals set out in 1999 by the UN, Corporate Social Responsibility (CSR) under the framework of ISO 26000, 2011 and the Objectives for Sustainable Development Goals Agenda 2030, 2015, Mexico's Business Sector has been taking full relevance in the triple Bottom Line actions (economic, social and environmental). This study shows the results of a questionnaire structured under the ISO 26000 reference framework, designed by ResPonsable, which was applied to a representative sample of the Mexican Business Sector in 2013-2019, to describe, infer and project the degree of knowledge, interest and management of CSR in large companies and MSMEs in Mexico. The main results are flattering since companies during these six years (2013-2019) have decided to create CSR Committees, this being more frequent in large companies and have an annual budget for Social Responsibility activities, with more trained managers in the area, and with more knowledge, importance and maturity of CSR. The term Social Responsibility has evolved as an investment and not as an expense for large companies, while MiPymes still see it as an expense. It is possible to see a decline in CSR indicators as a profitable investment in the short, medium and long term. Concerning the CSR employees’ profile, the positions are vastly occupied by women, between 32 and 42 years, with a professional education level with CSR studies. The most active sector in the CSR is transportation and logistics, banking, energy and extractive industry, food and beverage, automotive and construction and infrastructure, focusing on labor practices, environment and human rights, being Corporate Governance the least developed in the companies.